AB0465 Association between safety, efficacy and hydroxychloroquine dosage in the treatment of cutaneous lupus erythematosus and systemic lupus erythematosus. (15th June 2017) - Wakiya, R; Kameda, T; Izumikawa, M; Nakashima, S; Shimada, H; Ozaki, H; Kondo, A; Kadowaki, N; Dobashi, H
Abstract : Background: Hydroxychloroquine (HCQ) are considered to be effective against cutaneous lupus erythematosus (CLE) and symptoms associated with systemic lupus erythematosus (SLE) such as rashes, joint pain, and fatigue. In a randomized controlled trial in stable active patients with SLE on HCQ treatment, those who achieved blood HCQ levels greater than or equal to 1000ng/ml had a tendency for reduced SLE flares during a 7 month period [1]. To prevent ocular toxicity, HCQ should be maintained at a dose of 6.5mg/kg or less for ideal body weight [2], however, optimal HCQ dosage is unclear. Objectives: To extract the problem of the dosage based on ideal body weight and identify safer and more effective HCQ dosage. Methods: We enrolled patients who took HCQ for SLE or CLE more than 3 months in our institute and 2 related facilities from September 2015. We used Cutaneous Lupus Erythematous Disease Area and Severity Index (CLASI) to evaluate cutaneous symptoms and evaluated effect at start of administration and 3 months of that. The attending doctors assessed the adverse events (AEs). We investigated the change of serum biomarker, such as the value of serum complement and anti-ds-DNA body, the number of white blood cells, lymphocytes and platelets. Results: We enrolled the 30 patients with administration of HCQ more than 3 months and in CLE were 2 cases, in SLE were 28 cases. In 21 cases HCQ dosage were based on ideal weight. The AEs were in 13/30 cases (43.3%). The AEs were the new cutaneous symptoms in 5 cases, eye manifestation in 3 cases (abnormal visual field in 2 cases, color anomaly in 1 case), diarrhea in 2 cases, fever in 2 cases, feeling of fatigue in 2 cases, renal dysfunction in 1 case, muscular pain in 1 case, and pericarditis in 1 case. The eye manifestation in the 3 cases disappeared for a few days by stopping or reducing HCQ dosage. Although we needed glucocorticoid treatment for pericarditis, the other AEs improved by reducing HCQ dosage or stopping. The AEs of taking HCQ 200mg/day were in 6 cases, 200mg and 400mg alternatively on every other day in 6 cases, and 400mg/day in 1 case. The AEs of taking HCQ dosage based on ideal body weight were in 10/21 cases (47.6%) and by minimal dosage in 3/9 cases (33.3%). 22/28 cases (78.6%) significant improved cutaneous symptoms (amount of mean change of CLASI -4.57, p=0.024). There is no difference in the efficacy of cutaneous symptoms between group received HCQ based on ideal body weight (80.0%) and the others (92.3%). 5/21 cases of HCQ based on ideal body weight were made to reduce HCQ dosage due to AEs, but all 5 cases improved cutaneous symptoms. 53.3% (16/30) cases increased complement, but other biomarkers didn't change. Conclusions: HCQ was effective for the treatment of CLE even when HCQ dosage was reduced due to AEs. These findings suggest that low-dose HCQ is also effective and safe, and HCQ initial dosage wasn't the need to adjust for ideal body weight. References: Costedoat-Chalumeau N, et al. Hydroxychloroquine in systemic lupus erythematosus: results of a French multicentre controlled trial (PLUS Study). Ann Rheum Dis. 2013;72(11):1786–92. Ronald B. Melles, Michael F.Marmor. The risk of toxic retinopathy in patients on long-term hydroxychloroquine therapy. JAMA Ophthalmol. 2014;132(12):1453–60. Disclosure of Interest: None declared